2017
DOI: 10.1097/ccm.0000000000002061
|View full text |Cite
|
Sign up to set email alerts
|

Patient Eligibility for Randomized Controlled Trials in Critical Care Medicine: An International Two-Center Observational Study*

Abstract: Slightly more than half of the patients assessed were not eligible for enrollment in any of 15 major randomized controlled trials in critical care, most often due to the absence of the specific clinical condition of study. The majority of patients who met criteria for a randomized controlled trial did so on the first day of ICU admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…This is also borne out by recruiters more commonly experiencing patients being incorrectly excluded from trials than incorrectly included. This links to the recognised problem of limited generalisability of trial results, observed across various trial settings 10,19,[37][38][39][40][41][42] and for at least the last few decades. 17,43 Although other factors may contribute towards limited generalisability (such as recruiter discomfort in approaching some eligible patients 44 or underlying problems with the feasibility of interventions 45 ), speci c exclusions in eligibility criteria are likely to play a large part.…”
Section: Discussionmentioning
confidence: 99%
“…This is also borne out by recruiters more commonly experiencing patients being incorrectly excluded from trials than incorrectly included. This links to the recognised problem of limited generalisability of trial results, observed across various trial settings 10,19,[37][38][39][40][41][42] and for at least the last few decades. 17,43 Although other factors may contribute towards limited generalisability (such as recruiter discomfort in approaching some eligible patients 44 or underlying problems with the feasibility of interventions 45 ), speci c exclusions in eligibility criteria are likely to play a large part.…”
Section: Discussionmentioning
confidence: 99%
“…All RCTs have inclusion and exclusion criteria, which serves to identify patients with the illness and specifically exclude patients who are either unlikely to benefit or have a greater likelihood of harm from the trial treatment [9,25]. The sepsis RCTs mainly differ in terms of their exclusion criteria (eTable-3) [26], with similar inclusion criteria [27]. Therefore, we do not suggest that these principles are completely ignored in published sepsis trials where, for example, patients with metastatic cancer and cirrhosis are frequently excluded presumably because of the high non-sepsis attributable mortality of critical illness in these subsets (eTable-3) (20).…”
Section: Discussionmentioning
confidence: 99%
“…8 INSERM CIC 1432, Clinical Epidemiology, University of Burgundy, Dijon, France. 9 Medical-Surgical Intensive Care Unit, General Hospital Center, Saint Brieuc, France. 10 Medical-Surgical Intensive Care Unit, General Hospital Center, Le Mans, France.…”
Section: Supplementary Informationmentioning
confidence: 99%